The Urgency of Legal Reform in Ensuring Consumer Protection in E-Commerce Transactions in Indonesia - Zaenul Haq (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Article history: The advancement of digital technology has brought significant changes to trade transaction patterns, particularly through e-commerce. While online transactions offer convenience and efficiency, consumers face various risks such as fraud, product quality uncertainty, and data privacy breaches. This article analyzes legal protection for consumers in electronic transactions in Indonesia based on the Consumer Protection Act (UUPK) and the Electronic Information and Transactions Act (UU ITE). The research employs a normative-descriptive legal approach and literature review, focusing on civil law regulations regarding online sales agreements. The findings indicate that existing regulations, although relevant, still face implementation challenges, including personal data protection and digital dispute resolution. Recommendations include regulatory updates, strengthening legal oversight, and consumer education to establish a transparent, safe, and fair electronic transaction ecosystem.